(untitled) (Journal of EAHIL, 2020)
The coronavirus pandemic changed the days rather dramatically for the universities in March this year and still does. In the Medical Library at Umeå University we had to change the library service in many ways from one week to another. This article shows how we managed to have the library open for our customers; while keeping students, faculty and hospital staff safe. We did not close down as libraries in many countries did and also many university libraries in Sweden.